Vehicle routing problem for minimizing consumption of energy in three dimensional space - Hajar Ghahremani-Gol; Farzad Didehvar; Asadollah Razavi (Kuwait Journal of Science)
The vehicle routing problem VRP is usually studied in two dimensional Euclideanspaces. In this paper a variant of VRP was proposed, when the points are lying in thethree dimensional space, as it is often the case in the real problem. The cost matrix ofthe consumed energy was not symmetric. The minimum cost of total consumed energywas determined by identical vehicles. A new method was presented to compute thedistance between every two points and the consumed energy.